ISH NIA PS 01-03 Trichostatin A Inhibits Angiotensin II-induced Hypertension Via p66shc Dephosphorylation. (September 2016) - LEE, Yu Ran; Kang, Gun; Joo, Hee Kyoung; Park, Myoung Soo; Kim, Cuk-Seong; Choi, Sunga; Jeon, Byeong Hwa
Abstract : Objective: Histone deacetylases (HDACs) regulate cellular homeostasis via post-translational modification as well as through transcriptional gene regulation. It was recently reported that HDAC affects vascular inflammatory responses and promotes hypertension. However, the effect of the HDAC inhibitor, trichostatin A (TSA), on vasoreactivity and hypertension remains unknown. p66shc is phosphorylated on serine 36, and this phosphorylation event is essential to its function in the regulation of cellular ROS levels in endothelial cells (EC) and vascular smooth muscle cells (VSMC). Increased phosphorylation of p66shc is an important adaptive signal mediator in rats with aortic coarctation. Design and Method: We performed aortic coarctation at the inter-renal level in rats in order to create a hypertensive rat model. Results: Nicotinamide adenine dinucleotide phosphate-driven reactive oxygen species production was also reduced in the aortas of TSA-treated aortic coarctation rats. The vasoconstriction induced by angiotensin II (Ang II, 100 nM) was inhibited by TSA in both endothelium-intact and endothelium-denuded rat aortas, suggesting that TSA has mainly acted in vascular smooth muscle cells (VSMCs). In cultured rat aortic VSMCs, Ang II increased p66shc phosphorylation, which was inhibited by the Ang II receptor type I (AT1R) inhibitor, valsartan (10 μM), but not by the AT2R inhibitor, PD123319. TSA (1∼10 μM) inhibited Ang II-induced p66shc phosphorylation in VSMCs and in HEK293T cells expressing AT1R. Conclusions: Tthese results suggest that TSA treatment inhibited vasoconstriction and hypertension via inhibition of Ang II-induced phosphorylation of p66shc through AT1R.